Cute clothes for the crafty fashionista - Dybvik, Tina (Mankato, Minn Capstone Press, 2012)
"Step-by-step instructions for T-shirts, jeans, skirts, and other clothing crafts made from repurposed materials"--
Arts (handcrafts)
Includes bibliographical references (p. 31) and index
1 2 13 15
Keywords: Clothing and dress -- Remaking -- Juvenile literature